Effect of hydroxyl intercalation on tribological properties of MXene (Ti3C2Tx). Issue 21 (1st November 2021) - Tian, Pei; Yu, Guomin; Wei, Kongxia; Zhang, Zhenxi; Wang, Nong
Abstract: MXenes (Tin+1 Cn Tx ), a class of two-dimensional materials, have recently attracted the attention of many researchers in the field of lubrication owing to their low shear strength and self-lubrication ability. However, because of their weak adhesion, they fail quickly on metal surfaces. Ti- in an MXene can bond to functionalized –OH to form a Ti–OH terminal, which can enhance the binding force of MXene/metal interfaces. In this study, an MXene-ethylene glycol solid-liquid composite coating was designed. The ball-on-disc friction test results showed that the composite coating achieved a coefficient of friction of 0.165, which is 72.5% lower than that of the non-lubricated substrate. This is because the intercalation of hydroxyl groups in glycol allows MXene to better maintain its two-dimensional nanostructure. Moreover, the frictional performance of the composite coating under different loads was studied; the coefficient of friction further reduced to 0.147 at 8 N.